2005
DOI: 10.1158/0008-5472.can-05-1024
|View full text |Cite
|
Sign up to set email alerts
|

Misregulated Wnt/β-Catenin Signaling Leads to Ovarian Granulosa Cell Tumor Development

Abstract: Misregulation of the Wnt/B-catenin signaling pathway is a hallmark of several forms of cancer. Components of the Wnt/ B-catenin pathway are expressed in ovarian granulosa cells; nevertheless, its potential involvement in granulosa cell tumorigenesis has not been examined. To this end, human (n = 6) and equine (n = 18) granulosa cell tumors (GCT) were analyzed for B-catenin expression by immunohistochemistry. Unlike granulosa cells of normal ovaries, most (15 of 24) GCT samples showed nuclear localization of B-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
130
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 48 publications
21
130
1
Order By: Relevance
“…Specifically, ␤-catenin regulates transcription of the central player of estrogen biosynthesis, CYP19A1, via functional interactions with SF1. Prior reports of ␤-catenin-dependent gene expression in the gonad have been interpreted as evidence for the influence of Wnt signaling (30,31,33). We now extend these observations by demonstrating that ␤-catenin is essential for the ability of SF1 to respond to FSH.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Specifically, ␤-catenin regulates transcription of the central player of estrogen biosynthesis, CYP19A1, via functional interactions with SF1. Prior reports of ␤-catenin-dependent gene expression in the gonad have been interpreted as evidence for the influence of Wnt signaling (30,31,33). We now extend these observations by demonstrating that ␤-catenin is essential for the ability of SF1 to respond to FSH.…”
Section: Discussionsupporting
confidence: 76%
“…As a mediator of Wnt signaling, ␤-catenin regulates numerous genes involved in development and tumorigenesis (32). Recently, mice that express a constitutively active ␤-catenin mutation only in granulosa cells (GCs) were found to be subfertile and develop GC tumors (33). A role for Wnt signaling and ␤-catenin in embryonic gonad lineage specification has also been suggested (30,31).…”
mentioning
confidence: 99%
“…Wnt signalling has been found to be involved in both normal and tumourigenic development of the ovaries [70]; which includes folliculogenesis, luteogenesis, and steroidogenesis, and also tumourigenesis of granulosa cells [71,72]. Wnt ligands are widely expressed in the ovaries [73], are essential for ovarian follicular development and fertility [74], and also contribute to ovarian tumourigenesis through the canonical Wnt signalling pathway [75].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Wnt/β-catenin signaling maintains stemness in stem cells from different tissues and prevents them from differentiating [36,70]. For mouse GCs it was demonstrated that WNT2 protein regulates their proliferation through β-catenin pathway [18,81] which when misregulated can lead to ovarian granulosa cell tumor (GCT) [5].…”
Section: Telomerase Activity and Stemness In Granulosa Cellsmentioning
confidence: 99%